Solitary Fibrous Tumor of the Prostate Which Was Initially Misdiagnosed as Prostate Cancer - Soma Osamu; Hiromi Murasawa; Atsushi Imai; Shingo Hatakeyama; Takahiro Yoneyama; Yasuhiro Hashimoto; Takuya Koie; Chikara Ohyama (Case Reports in Urology)
Solitary fibrous tumor (SFT) of the prostate is a very rare tumor. We report a case of 65-year-old man with SFT of the prostate which was initially misdiagnosed as prostate cancer. Finally, we performed total prostatectomy and the tumor was histologically diagnosed as SFT of the prostate. The patient’s clinical course has progressed favorably with no obvious recurrence 18 months postoperatively.